Implementation of the Pancasila Student Profile Strengthening Project in Enhancing Students' Civic Skills in Community Engagement - Hikmatyar, Alvin (Universitas Pendidikan Indonesia (UPI), 2024)
This study aims to examine the role of the Pancasila Student Profile Strengthening Project in enhancing students' civic skills in their community life. In an era of globalization characterized by numerous challenges, it is crucial for the younger generation to possess robust civic skills to actively participate in the social, political, and economic life of the nation. This research employs a qualitative approach with a case study method, involving observation, interviews, and document analysis. The results indicate that the implementation of the Pancasila Student Profile Strengthening Project significantly improves students' understanding, skills, and attitudes towards Pancasila values, which are then reflected in their community activities. This study recommends that the Pancasila Student Profile Strengthening Program be integrated into the national education curriculum to develop a generation that is not only academically proficient but also responsible as good citizens.